Utilization of Health Applications Among Patients Diagnosed with Chronic Diseases in Jazan, Saudi Arabia During the COVID-19 Pandemic - Alharbi R; Qadri A; Mahnashi M; Hakami A; Darraj B; Shnaimer J; Gosadi I (Patient Preference and Adherence, 2021)
Ruwaym Alharbi,1 Alanood Qadri,1 Mashael Mahnashi,1 Alshomokh Hakami,1 Bushra Darraj,1 Jubran Shnaimer,2 Ibrahim Gosadi3 1Faculty of Medicine, Jazan University, Jazan, Saudi Arabia; 2Family Medicine Department, Jazan Health Affairs, Ministry of Health, Jazan, Saudi Arabia; 3Department of Family and Community Medicine, Faculty of Medicine, Jazan University, Jazan, Saudi ArabiaCorrespondence: Ibrahim GosadiFaculty of Medicine, Jazan University, P.O. Box: 2349, Jazan, 82621, Saudi ArabiaTel +966 562137711Email gossady@hotmail.comPurpose: Health applications are employed to aid patients with chronic diseases in effective long-term disease management. This investigation aims to measure the utilization of health applications among patients diagnosed with chronic conditions during the COVID-19 pandemic.Methods: This cross-sectional investigation was conducted in the Jazan region in Saudi Arabia between October 2020 and March 2021. Data were collected during interviews using a semi-structured questionnaire. The questionnaire collected items about the patients’ demographics, morbidity, and use of electronic devices and health applications developed by the Saudi MoH. Logistic regression was used to assess factors associated with odds of reporting use of applications.Results: A total of 658 patients were recruited. The mean age of the patients was 51 years, and 59% of them were females. The most frequently reported diagnosed condition was diabetes (53.5%), followed by hypertension (42.7%). Majority of the patients reported not using any health applications developed by the Saudi MoH (68.2%). Patients with higher educational levels and younger patients were more likely to report use of the applications (ORs: 4.2, 2.6 respectively). Comorbidity history and disease duration did not seem to influence the probability of reporting use of health applications (P-values > 0.05).Conclusion: Patients diagnosed with chronic diseases in Jazan had low utilization of health applications developed by the Saudi MoH. This indicates a need to encourage the use of these health applications, particularly among patients with chronic diseases and to consider use restriction among older patients with lower educational levels.Keywords: health applications, chronic diseases, diabetes, hypertension, COVID-19, Jazan, Saudi Arabia